Prevalence and Social-Ecological Correlates of Intimate Partner Violence in a Conflict Zone—Evidence From the 2015 Afghanistan Demographic and Health Survey - Alemi, Qais (Violence against women, 2022)
This study examined the prevalence and social-ecological correlates of male-to-female intimate partner violence (IPV) in Afghanistan. Using data from the 2015 Afghanistan Demographic and Health Survey, which included 20,793 currently married women, we found that the past-year prevalence of physical IPV was highest (46%), followed by emotional (34%) and sexual forms (6%). Results also showed that the risk of IPV in general was associated with an array of community and societal-, family and relationship-, and person-level factors. Our findings point to potential intervention targets for women in this conflict zone where IPV is a highly pervasive and complex societal challenge.